2021
DOI: 10.1007/s13157-021-01505-7
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Covid-19 on Perceived Health Effects of Wetland Parks in China

Abstract: Wetland parks are designed to support urban ecological protection, flood control and human well-being. Existing research mainly focuses on their influence on ecology and economy. However, their influence on human well-being and health is rarely studied. In China, during the peak of the COVID-19 pandemic (Peak), people were very concerned about health, while at the same time wetland parks which are generally considered beneficial to health were closed. Thus, this study explores the public’s perception of the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…According to the literature, an individual’s health is influenced by environmental factors, sociodemographic characteristics, and psychological traits ( 18 , 39 , 42 , 43 ). Dispositional optimism is a positive psychological trait often associated with good health and relief from stress and anxiety ( 44 ).…”
Section: Conceptual Framework and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, an individual’s health is influenced by environmental factors, sociodemographic characteristics, and psychological traits ( 18 , 39 , 42 , 43 ). Dispositional optimism is a positive psychological trait often associated with good health and relief from stress and anxiety ( 44 ).…”
Section: Conceptual Framework and Hypothesismentioning
confidence: 99%
“…However, it cannot be simply determined a priori from the relevant observed variables because the unobserved heterogeneity in an individual’s perception is not necessarily captured by the variables preconceived and specified by existing theoretical and conceptual models, but it can exist outside of the previously identified variables ( 47 ). For example, the results of various studies on gender differences in health perceptions in wetland parks are mixed: Some studies have found no significant differences in health perceptions between men and women who visited wetland parks before and after the outbreak ( 39 ), while others have shown that women who visited nature reserves felt healthier than men ( 48 ). It is imperative to classify heterogeneous visitors into multiple homogeneous groups and identify appropriate treatments for wetland park planning and design.…”
Section: Conceptual Framework and Hypothesismentioning
confidence: 99%
“…Sobre esto último, la pandemia ha revelado más evidencias empíricas sobre los beneficios de este tipo parques en la salud de las personas. En China, el cierre de parques en humedales y la limitación para acceder a estos espacios aumentó la percepción de los usuarios respecto a los beneficios psicológicos que traía visitarlos en un año normal (Zhai y Lange, 2021). Por consiguiente, los humedales urbanos representan una alternativa concreta para el desarrollo de proyectos de infraestructura verdeazul para la recreación, la biodiversidad y el bienestar de las personas, en especial en ciudades con déficit de áreas verdes.…”
Section: El Valor De Acceder a Los Humedales Urbanosunclassified
“…Hoy en día los humedales están en un serio proceso de desaparición mundial (Darrah et al, 2019) que preocupa notoriamente dado que existen múltiples evidencias de sus innumerables beneficios para las personas y los hábitats: mitigan inundaciones, protegen a la costa de la erosión, son hábitats de biodiversidad, limpian el aire, secuestran carbono, entre otras contribuciones (Basu et al, 2021;Dabrowska-Zielinska et al, 2014;Penatti, Ribeiro, Ferreira, Arantes y Coe, 2015). En efecto, últimamente se les está valorando como soluciones basadas en la naturaleza, para resolver la problemática de las inundaciones urbanas, como también para incrementar el diseño de parques urbanos orientados al bien común (Zhai y Lange, 2021).…”
Section: Introductionunclassified
“…With support from the public, they aim to encourage the UK government to prioritise wetland creation, to address the environmental and social crises that exist today (WWT 2021 ). In the context of COVID-19 or potential future pandemics, urban wetlands have recently been promoted as a means of promoting public health (Zhai and Lange 2021 ). In particular, urban wetlands, as a key urban biodiversity space, can provide recreation while also promoting residents' mental and physical health and making cities more livable (Andreucci et al 2019 ; Russo and Cirella 2020 ; Russo and Holzer 2021 ; Rojas et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%